Interactive learning innovation: implementing wordwall and quizizz in learning multimedia training - Riana Antika Amahoroe (12 Waiheru, 2025)
This study aims to evaluate the implementation of integrating Wordwall and Quizizz to enhance teachers’ skills and productivity in creating interactive quizzes. An initial survey of participants from the first distance learning multimedia training cohort revealed that 100% had never used either application. Consequently, this study was structured to guide teachers in creating accounts, designing interactive quizzes, and simulating the use of both platforms. The research follows a qualitative approach, utilizing descriptive surveys, observations, and interviews. The sample includes 30 teachers from various districts and cities in Maluku and North Maluku, who participated in six days of online training. The research was carried out in three phases: preparation, implementation, and evaluation. Results indicated that 80% of participants successfully created interactive quizzes using Wordwall and Quizizz, while the remaining 20% gained an understanding of their use. Implementing interactive quizzes in the classroom made a more dynamic and engaging learning environment, boosting participants’ enthusiasm and motivation—the wide range of templates available on both platforms allowed for the quick and innovative creation of quizzes. In conclusion, integrating Wordwall and Quizizz significantly improves teachers’ skills and productivity, positively impacting the learning experience.